Analysis of Factors Affecting Shopping Levels Independent Student Exchange Program Batch 3, Universitas Negeri Medan - Alvindra, Devira Chessa; Pambudi, Setyari; Andriani, Dwi Nila; Wibawa, Ramadhan Prasetya (Universitas PGRI Madiun, 2024)
The Independent Student Exchange Program (PMM) is one of the Merdeka Belajar Kampus Merdeka (MBKM) activities that aim to enrich student learning experiences. Students are active individuals who always try to meet their needs, especially students who are taking part in programs from their universities or the government, for example, the Independent Student Exchange (PMM) program. This article aims to find out what factors can influence the consumption level of exchange students. This research uses a qualitative descriptive method, and the instruments of this research are students from the Independent Student Exchange Program (PMM) batch 3, Universitas Negeri Medan. The results obtained from this research are pocket money, scholarships, basic needs, primary needs, and the completeness of goods and services available at the location where the exchange student lives.